EFFECTIVENESS OF TACTILE KINESTHETIC STIMULATION ON THE STABILITY OF PREMATURE INFANT VITAL SIGNS: EFEKTIFITAS STIMULASI TAKTIL KINESTETIK TERHADAP KESTABILAN TANDA VITAL BAYI PREMATUR - Sudaryanto; Muhammad Sowwam (Universitas Duta Bangsa Surakarta, 2023)
Background: Premature babies are babies born at less than 37 weeks of gestation counting from the last menstrual period. In premature babies with insufficient gestational age, the organ systems of premature babies are not yet perfect so that they will have difficulty adapting to life outside the uterus. WHO data in 2017 states that 7000 newborns in the world die every day. The incidence of premature and premature infant mortality in Indonesia is still relatively high. Indonesia is ranked in the top 10 out of 184 countries with a high incidence of premature birth, which is 15.5 premature births per 100 live births. Objective: Knowing the effectiveness of tactile kinesthetic stimulation on the stability of the vital signs of premature babies. Methods: This type of research is quantitative with a quasi-experimental approach with a research design that is a two group pretest-posttest design. Results: There is a significant difference in vital signs, temperature with p value 0.003, pulse rate with p value 0.014, Respiration Rate with p value 0.000 and oxygen saturation with p value 0.003 in premature infants in the control group (without tactile kinesthetic stimulation treatment) with the intervention group (premature babies who are treated with tactile kinesthetic stimulation). Conclusion: There are significant differences in vital signs (temperature, pulse, Respiration Rate and oxygen saturation) in premature infants in the control group (without tactile-kinesthetic stimulation treatment) and the intervention group (premature infants receiving kinesthetic tactile stimulation treatment).